Signatures of pancake bonding in hydrated eumelanin - Bernard Mostert (Physical Chemistry Chemical Physics, 2023)
Pancake bonding phenomenology is applied for the first time in a bioorganic system, the pigment eumelanin, via a hydration-induced decrease of the interplanar distance down to 3.19 Å. The observation explains the long-term inconsistency between electron paramagnetic resonance and muon spin relaxation data for eumelanin.